2018
DOI: 10.31234/osf.io/8wzmt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The forward effect of testing: Behavioral evidence for the reset-of-encoding hypothesis using serial position analysis

Abstract: The forward effect of testing refers to the finding that retrieval practice of previously studied information increases retention of subsequently studied other information. It has recently been hypothesized that the forward effect (partly) reflects the result of a reset-of-encoding (ROE) process. The proposal is that encoding efficacy decreases with an increase in study material, but testing of previously studied information resets the encoding process and makes the encoding of the subsequently studied informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Retrieval can potentiate new learning by increasing learners' attention to subsequent material (Pastötter et al, 2018;Pastötter et al, 2011;Szpunar, 2017) and improving their encoding/retrieval strategies (Chan et al, 2018b;Soderstrom & Bjork, 2014). In the present study, we used participants' reported test expectancy ratings and semantic clustering scores to provide a quantitative estimate of attention-based and strategy-based processes, respectively.…”
Section: Retrieval Potentiates New Learning Through Attention-based A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Retrieval can potentiate new learning by increasing learners' attention to subsequent material (Pastötter et al, 2018;Pastötter et al, 2011;Szpunar, 2017) and improving their encoding/retrieval strategies (Chan et al, 2018b;Soderstrom & Bjork, 2014). In the present study, we used participants' reported test expectancy ratings and semantic clustering scores to provide a quantitative estimate of attention-based and strategy-based processes, respectively.…”
Section: Retrieval Potentiates New Learning Through Attention-based A...mentioning
confidence: 99%
“…The association between continuous episodic encoding and inattention is further illustrated through electrophysiological evidence, where alpha-band oscillations, an EEG indicator of inattention (Palva & Palva, 2007;Klimesch, 2012), rise with encoding, but this increase is abolished with interpolated retrieval practice (Pastötter, Schicker, Niedernhuber, & Bauml, 2011). This encoding-induced inattention can manifest through increasingly frequent bouts of mind wandering (Szpunar et al, 2013) and reduced capacity to learn new information (Pastötter, Engel, & Frings, 2018;Pastötter et al, 2011). When students are asked to retrieve previously studied material, however, the change in the task demand may halt further inattention by forcing learners to orient their attention back toward the target material (Davis & Chan, 2015;Davis, Chan, & Wilford, 2017;Pastötter et al, 2018).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The forward effect is typically attributed to PI reduction. The idea is that recall testing between the study of lists promotes contextual list segregation, which may enhance temporal differentiation between preceding and critical lists at test (Bäuml & Kliegl, 2013;Divis & Benjamin, 2014;Szpunar et al, 2008) and may also increase attentional resources during critical list encoding (Pastötter et al, 2011;Pastötter, Engel, & Frings, 2018). The forward effect is a robust phenomenon that has been replicated in a number of studies employing different item materials and different experimental settings (for reviews, see Pastötter & Bäuml, 2014;Yang, Potts, & Shanks, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…4. A study byPastötter et al (2018) recently examined the forward effect of testing on immediate list 3 recall in 240 younger university students when employing an experimental setup that was similar to the present one. Effect size calculation of Cohen's for nonrepeated measures revealed a medium effect size for the forward effect, regarding both correct recall, = .614, and number of prior-list intrusions, = .396.…”
mentioning
confidence: 99%